2020
DOI: 10.1096/fj.201902967r
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin destabilizes NOX2 mRNA and protects dopaminergic neurons from oxidative damage in Parkinson's disease

Abstract: Tristetraprolin (TTP), an RNA-binding protein encoded by the ZFP36 gene, is vital for neural differentiation; however, its involvement in neurodegenerative diseases such as Parkinson's disease (PD) remains unclear. To explore the role of TTP in PD, an in vitro 1-methyl-4-phenylpyridinium (MPP +) cell model and an in vivo 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) of PD were used. Transfection of small interfering (si)-TTP RNA upregulated pro-oxidative NOX2 expression and ROS formation, downregulated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Mounting evidence has shown that microglial NOX2 contributes to CNS OS and neuronal damage. NOX2-containing NADPH oxidases have emerged as a major source of OS in PD ( Gao et al, 2003a ; Qin et al, 2004 ; Wu et al, 2005 ; Kim et al, 2007 ; Gao et al, 2012 ; Marrali et al, 2018 ; Sun et al, 2020 ) ( Figure 5 ). NOX2 is expressed in several regions of the brain and various cell types, including neurons at the striatum ( McCann et al, 2008 ; Guemez-Gamboa et al, 2011 ), substantia nigra ( Zawada et al, 2011 ; Qin et al, 2013 ), and midbrain ( Qin et al, 2013 ), and is heavily expressed in microglia than in neurons and astroglia.…”
Section: The Sources Of Oxidative Stress In Parkinson’s Diseasementioning
confidence: 99%
“…Mounting evidence has shown that microglial NOX2 contributes to CNS OS and neuronal damage. NOX2-containing NADPH oxidases have emerged as a major source of OS in PD ( Gao et al, 2003a ; Qin et al, 2004 ; Wu et al, 2005 ; Kim et al, 2007 ; Gao et al, 2012 ; Marrali et al, 2018 ; Sun et al, 2020 ) ( Figure 5 ). NOX2 is expressed in several regions of the brain and various cell types, including neurons at the striatum ( McCann et al, 2008 ; Guemez-Gamboa et al, 2011 ), substantia nigra ( Zawada et al, 2011 ; Qin et al, 2013 ), and midbrain ( Qin et al, 2013 ), and is heavily expressed in microglia than in neurons and astroglia.…”
Section: The Sources Of Oxidative Stress In Parkinson’s Diseasementioning
confidence: 99%
“…Mice were divided into four groups (15 per group), with each group receiving recombinant lentiviruses containing LV-oe-EGR1, LV-oe-NC (HanBio, Shanghai, China), miR-381 agomir, or agomir NC (GenePharma, Shanghai, China) at the SNc. The injection site at SNc was identified by the following stereotaxic coordinates: 3.08 mm posterior of the bregma, 1.01 mm from the midline, and 4.45 mm from the skull . Lentivirus (2 μL, 2 × 10 5 TU/μL) was injected with a microinjector at a rate of 0.25 μL/min.…”
Section: Methodsmentioning
confidence: 99%
“…AntagomiR-214-3p, lentivirus-packaged oe-HSF1 (LV-oe-HSF1), lentivirus-packaged oe-NFATc2 (LV-oe-NFATc2), and the corresponding controls were all provided by GenePharma (Shanghai, China) and stereotaxically injected into mice according to the previous method [34]. Briefly, after anaesthesia, the mouse was fixed on a stereotaxic apparatus (Render Biotech Co., Ltd, Shenzhen, China) and a hole was drilled for single unilateral injection at the following stereotactic coordinates: 3.0 mm anteroposterior from bregma; 1.2 mm mediolateral from bregma; 5.0 mm dorsoventral from bregma.…”
Section: Stereotaxic Injectionmentioning
confidence: 99%